2018
DOI: 10.3892/etm.2018.6231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of changes in IL-6, CRP and S100 in serum and NO in cerebrospinal fluid in subarachnoid hemorrhage and prognosis

Abstract: Clinical significance of changes in interleukin-6 (IL-6), C-reactive protein (CRP) and S100 in serum and NO was investigated in cerebrospinal fluid (CSF) in subarachnoid hemorrhage (SAH) and its prognosis. A total of 43 SAH patients and 23 healthy subjects were selected and divided into cerebral vasospasm (CVS) group and non-CVS group, and favorable prognosis group and unfavorable prognosis group according to Hunt-Hess grade. The levels of IL-6, CRP, S100 and NO in CSF were detected, respectively, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Several inflammatory cytokines have been found to be linked to aSAH [21]. IL-6 plays an important role in brain injury, and associated with aSAH in numerous studies [23,26,30]. A previous study showed that IL-6 in cerebrospinal fluid (CSF) was a biomarker for predicting vasospasm after SAH [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several inflammatory cytokines have been found to be linked to aSAH [21]. IL-6 plays an important role in brain injury, and associated with aSAH in numerous studies [23,26,30]. A previous study showed that IL-6 in cerebrospinal fluid (CSF) was a biomarker for predicting vasospasm after SAH [31].…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study showed that IL-6 in CSF could be a useful diagnostic tool for predicting shunt dependency in aSAH patients with acute hydrocephalus [33]. Serum IL-6 levels were elevated, and were associated with prognosis in aSAH patients [26,34]. However, many previous studies also showed that determining the IL-6 levels in blood circulation may not be sufficient [30,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in ammatory cytokines have been found to be linked to aSAH [21]. As a well-known cytokine, IL-6 play an important role in brain injury, and associated with aSAH in numerous studies [23,26,30]. Previous study showed that IL-6 in cerebrospinal uid (CSF) seem to be a biomarker for predicting vasospasm after SAH [31].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a proin ammatory cytokine in response to acute brain injury and other diseases [17,24,25]. Several studies have demonstrated elevated IL-6 levels may induce neuroin ammation and may be closely associated with the prognosis of aSAH patients [23,26,27].…”
mentioning
confidence: 99%